Modeling of an Herbivorous Digestive System as a 3-Continuous Stirred Tank Reactor (CSTR) -1-Plug Flow Reactor (Per) Arrangement with Particular Reference to Hippopotamus Amphibious - Awolu, Olugbenga Olufemi (2015)
Hippopotamus Amphibious has three stomach compartments together with small and large intestines all required in digesting lignocellulosics. It is desirable to model the performance of such a natural (in - vivo) system with the view to designing a physical (in-vitro) system for efficient digestion of lignocellulosics.